Understanding user needs and seeking behavior in the age of information revolution: A case of university library in the southern part of Bangladesh - Atikuzzaman, Md.; Mostofa, SK Mamun; Tabassum, Mashiat (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: Information has become a powerful element that shapes our thoughts, decisions, opinions and holistic approach towards life. The requirement for information ranges from personal and professional development to social survival Purpose: The main purpose of this study is to assess the information needs and information-seeking behavior of the users of a southern public university library in Bangladesh. Method: A quantitative approach was used to explain the information-seeking behavior of the student-users of the target library. A structured questionnaire was used to collect data from the users/students. A simple random sampling technique was used to reach the target population. The link to the questionnaire was sent to almost 350 students and finally, 205 responses were retrieved with a response rate of 58.5%. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. Findings: The study discovered that students of Noakhali Science and Technology University (NSTU) mostly use the library for studying and internet access. Library books are the most popular resource. Obstacles to information access, including a scarcity of book copies, inexperience with the library catalog, and a perception of insufficient resources, were major barriers to seeking information. The present study revealed that gender did not have a major impact on the purposes of visiting the library. Significant differences were found between age groups, demonstrating that preferences change as students progress through their academic lives. Conclusion: The achieved findings are a new discovery for the students of the southern part of Bangladesh, as no previous studies have been published in this part of Bangladesh.